2020
DOI: 10.1177/0193945920942487
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Health-promoting Programs for Patients with Chronic Kidney Disease: Randomized Controlled Trial

Abstract: Research on dietary and lifestyle modifications to decrease cardiovascular risk and slow disease progression has been limited to patients in the later stages of chronic kidney disease (CKD). Studies on the effectiveness of stage-of-change-tailored interventions on lifestyle modifications for individuals with early stage CKD are limited. Using random assignment, 60 patients with early stage CKD who received up to six tailored intervention visits over 30 months were compared to 60 usual care patients on physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…Evidence supports the efficacy of interventions tailored to the stage of change of individuals for a variety of behavioral problems including eating behavior and physical activity (Marcus et al, 1998;Klöckner and Ofstad, 2017;Krebs et al, 2018;Teng et al, 2020). In the childhood overweight/obesity literature, the TTM has been applied as a helpful conceptual framework in a variety of quantitative studies (Rhee et al, 2005(Rhee et al, , 2014Sealy and Farmer, 2011;Giannisi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence supports the efficacy of interventions tailored to the stage of change of individuals for a variety of behavioral problems including eating behavior and physical activity (Marcus et al, 1998;Klöckner and Ofstad, 2017;Krebs et al, 2018;Teng et al, 2020). In the childhood overweight/obesity literature, the TTM has been applied as a helpful conceptual framework in a variety of quantitative studies (Rhee et al, 2005(Rhee et al, , 2014Sealy and Farmer, 2011;Giannisi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Nonsignificant improvements were reported in 90 domains across 14 studies. 28 , 29 , 30 , 35 , 36 , 39 , 42 , 44 , 45 , 47 , 54 , 58 , 78 , 79 , 88 , 90 No difference in QoL between intervention and control arms were reported for 3 domains across 3 studies, 47 , 49 , 58 whereas nonsignificant reductions in QoL after lifestyle interventions, compared with those of control, were reported in 17 domains across 10 studies. 36 , 43 , 44 , 45 , 47 , 49 , 54 , 58 , 78 , 79 , 88 No studies reported statistically significant reductions in QoL after lifestyle interventions, compared with those of the control.…”
Section: Resultsmentioning
confidence: 98%
“…The characteristics of the included studies are outlined in Table 2 , Table 3 , Table 4 , Table 5 . 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ,…”
Section: Resultsunclassified
See 2 more Smart Citations